Classes of Caregivers Feeding Practices and Associated Factors Among Preschoolers. (7th June 2021) - Rahmaty, Zahra; Johantgen, Mary M; Storr, Carla; Wang, Yan; Black, Maureen M
Abstract: Objectives: During early childhood, eating habits are formed, and excess weight gain may begin. Caregivers' feeding practices (FP) influence childhood obesity and may get influenced by cultural and economic considerations 5 6, as well as caregivers' perception of child's size and temperament 7 8 . FP are employed simultaneously, thus influencing each other 9 . There is limited evidence on implementing FP simultaneously and what factors are associated with them 2 . This study examined (1) the heterogeneity in FP among caregivers and (2) associated child, caregiver, and family factors. Methods: Caregivers of 466 preschoolers (55.4% boys, mean age of 48 months), enrolled in 50 childcare centers, completed the Comprehensive Feeding Practices Questionnaires (CFPQ), demographic information, and perceptions of their child's weight and temperament. From Exploratory Factor Analysis of the CFPQ items, we identified 13 factors and conducted latent profile analysis (LPA), identifying three classes. We used Structural Equation Modeling to regress the emergent classes on child sex, race, age, family's economic status, and education level, and on caregiver's perception of child weight and temperament. Results: Class 1 had high coercive control and low autonomy practices (69%), Class 2 had high coercive control, but moderate in balance and autonomy practices (16%), and Class 3 were moderate in all practices (15%). Caregiver's perception of child size was associated with classes ( P < .001). Among the 22.2% of caregivers who wanted their child to be heavier, 22.2% were in the restricting class, 8.6% were in the balanced class, and 68.8% were in the controlling group. Conclusions: FP are modifiable factors and may be a good target for obesity prevention interventions. In this sample, most caregivers reported using coercive control behaviors with low autonomy to promote preschooler's independent eating. Future plans are to relate FP classes to diet quality and obesity in children. Funding Sources: The mother study was funded by the National Institute of Diabetes and Digestive and Kidney Diseases [Grant number R01 DK107761; PI: Black]. This study was funded by Sigma (Pi at-Large Chapter).